Case report: Non-EBV associated cerebral vasculitis and cerebral hemorrhage in X-linked lymphoproliferative disease - Li, Bangtao; Chen, Weiming; Cai, Xiaodi; Hai, Yuanping; Pang, Qiming; Xiang, Wei; Zhang, Zhengzheng (Frontiers in Immunology, 2024)
X-linked lymphoproliferative disease (XLP) is a rare genetic disorder characterized by immune dysregulation. The three most common clinical phenotypes are EBV-associated infectious mononucleosis (FIM), abnormal gammaglobulinemia, and lymphoma. We present a rare case of XLP1 with neurovasculitis, which is non-EBV-related and involves multiple systems, a condition rarely seen in children.The patient initially presented with an unsteady gait, which progressively evolved into language and consciousness disorders. Additionally, CT scans revealed multiple nodules in the lungs. Subsequent genetic testing and brain tissue biopsy confirmed the diagnosis: XLP1-related cerebral vasculitis and cerebral hemorrhage. Tragically, during the diagnostic process, the child experienced a sudden cerebral hemorrhage and herniation, ultimately resulting in fatality. This case offers a comprehensive insight into XLP1-related cerebral vasculitis and cerebral hemorrhage, underscoring the significance of early diagnosis and prompt treatment, while also imparting valuable clinical experience and lessons to the medical community.